Osoba Ježíše jako předmět křesťansko-muslimského dialogu v díle A. K. Cragga - Radislav Novotný (Teologická Reflexe)
This article explores Albert Kenneth Cragg’s approach to the person of Jesus as a central subject in Christian-Muslim dialogue. Cragg sought to bridge theological gaps by engaging with Islamic Christology using Muslim terminology, emphasizing shared foundations while preserving Christian distinctiveness. He developed the concept of “hospitality”, advocating respectful interfaith engagement. His method – interpreting Christian theology through Islamic categories – was both innovative and controversial. Critics argued that it risked distorting Christian doctrine. The article highlights key themes in Cragg’s work, such as divine kenosis, prophetic authority, and God-human relations, demonstrating his pioneering role in interfaith dialogue.